My hero academia. 13 - Horikoshi, Kōhei, 1986-; Cook, Caleb D. (Shonen Jump manga., 2018)
The students of Class 1-A have reached another milestone--the Provisional Licensing Exam. After making it through the first part of the test, they ready themselves for the next phase, which takes place in a simulated disaster area. Midoriya and his friends have to rescue as many victims as they can, and although the students of rival Shiketsu High are technically supposed to be helping, competition between them is fierce and even dangerous! As the scenario unfolds and villains arrive to shake things up, the U.A. students will have to find new ways to work with each other and make use of their Quirks.